Star fruit leaves (Averrhoa bilimbi) extract and shrimp shell chitosan gel improves neovascularization in gingival wound healing in vivo - Prasetyaningrum, Nenny; Priana, Sekar Citra (Faculty of Dental Medicine Universitas Airlangga, 2024)
Background: Gingival incision is a procedure widely used in dentistry that can potentially cause infection. Star fruit leaves (Averrhoa bilimbi) extract contains saponins, tannins, flavonoids, and phenols that can act as antibacterials. Shrimpshells chitosan have good biocompatibility, biodegradability, non-toxicity, and antimicrobial properties. Star fruit leaves (A. bilimbi) extract and shrimp shell chitosan are made in gel preparations to accelerate drug delivery to target cells. Purpose: To specify the effect of applying a gel extract of star fruit leaves (A. bilimbi) and chitosan shrimp shells on the formation of new blood vessels in the healing process of gingival incision wounds. Methods: 25 males Rattus norvegicus needed to make an incision in the labial gingiva and were divided into five groups, namely the K-group (without any application), K+ (aloe vera gel application), and three treatment groups PI, PII, and PIII (5%, 10%, and 15% gel extract of Star fruit leaves (A. bilimbi) and shrimp shell chitosan). Topical application is carried out twice a day for seven days. Microscopic observations with hematoxylin-eosin staining were used to count the number of new blood vessels. The analysis used the one-way analysis of variance and the post-hoc Tukey Honest Significant Different method. Results: The treatment in the PII group showed significantly (p < 0.05) higher results than other groups. Conclusion: The formulation of 10% gel Star fruit leaves (A. bilimbi) extract and shrimp shells chitosan has increased blood vessels in the healing process of gingival incision wounds.